Decreased warfarin sensitivity among patients treated with elbasvir and grazoprevir for hepatitis C infection. (16th August 2019) - DeCarolis, Douglas D; Chen, Yi-Chieh; Westanmo, Anders D; Conley, Christopher; Gravely, Amy A; Khan, Fatima B
Abstract: Purpose: We previously reported an interaction with warfarin anticoagulation when initiating treatment with direct-acting antiviral agents for hepatitis C infection. A decreased warfarin sensitivity led to subtherapeutic anticoagulation. To study this interaction further, we expanded our research to include patients treated with the combination of elbasvir and grazoprevir concurrent with warfarin anticoagulation and investigated changes in warfarin sensitivity during and after treatment. Methods: Using electronic health records of the Veterans Health Administration, patients starting treatment with elbasvir–grazoprevir for hepatitis C infection concurrent with warfarin anticoagulation were identified. Inclusion required stable warfarin anticoagulation prior to 12 weeks of treatment with elbasvir–grazoprevir. A warfarin sensitivity index (WSI) was calculated at the start and end of treatment and 12 weeks after treatment. The primary endpoint was the difference in WSI from pre- to end-treatment. The secondary endpoint was the WSI difference from pretreatment to 12 weeks posttreatment. Changes in International Normalized Ratio, warfarin doses, and time in therapeutic range were measured. Results: In the final sample of 43 patients, the mean WSI decreased during treatment from 0.53 to 0.40, or 25.2%. After treatment, the mean WSI rose to 0.51. Although the mean weekly warfarin dose increased from 40.3 to 44.6 mg during treatment, the mean International Normalized Ratio decreased from 2.40 to 1.96, recovering to 2.59 after treatment. The time spent in therapeutic range decreased from 74.1% before treatment to 39.8% during treatment and back to 64.9% 12 weeks posttreatment. Conclusion: When elbasvir–grazoprevir was added to stable warfarin anticoagulation, warfarin sensitivity decreased significantly during treatment and returned to baseline after treatment.